2020
DOI: 10.1111/jog.14229
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analysis of accreta, increta and percreta cases using acoustic radiation force impulse elastography

Abstract: Objective: To compare acoustic radiation force impulse (ARFI) elastography values and histopathological diagnoses (accreta, increta, percreta) in patients suspected of having abnormal placental invasion (API). Materials and methods: This prospective study included 54 patients in the third trimester with a history of caesarian section (CS) and API based on gray scale and Doppler ultrasonography (USG) and 35 healthy controls. Patients underwent ARFI elastography preoperatively. Elastography measurements of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
“…After exclusion of duplicates and two articles that were not available, 880 remained, of which a further 793 were excluded after screening the titles and abstracts, as the data they reported were not relevant. The remaining 87 studies were retrieved for full-text review, of which 72 were excluded after in-depth review, leaving 15 studies describing eight new ultrasound signs for the prenatal evaluation of PAS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The process of selection of these articles is summarized in Figure S1, and the characteristics of the 15 studies identified by the systematic review are presented in Table S1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Although ultrasonography is an effective method for showing abnormal placental invasion, it does not provide sufficient information about the depth of invasion. Therefore, it is difficult to determine the abnormal invasion of the accreta, increta, and percreta groups by USG ( 15 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound elastography has been recently used in the obstetrics and gynecology field. Pregnant women with complications including IUGR, 12 preeclampsia, 15 cholestasis of pregnancy, 16 mild variations (single umbilical artery) in fetuses 17 and placental invasion anomalies 18 have been evaluated via placental elastography in recent studies. It has also been shown that there is a negative impact of obesity on placental tissue structure 19 .…”
Section: Discussionmentioning
confidence: 99%